Language of shock and present experience: Benjamin as a reader of Baudelaire - Chataignier, Gustavo; Souyris, Lorena (Estudios de Filosofía, 2025)
This article discusses Benjamin’s interpretation of Baudelaire’s poetry as a key to reading modernity. Understanding the ambiguities between novelty and archaism, typical of the time, is only possible thanks to the poet’s gesture of privileging radical contingency. On the one hand, the violence of unwanted encounters amid the crowd does not allow for reflection; on the other, its productive dimension makes contingency speakable. The poet’s verses will make possible the encounter of the now of experience with the available past in terms of expectation: explanatory images are produced from the singularity of language. Finally, the Lacanian real is produced thanks to the understanding of the psyche as structure.